High Optical Gain of Solution‐Processed Mixed‐Cation CsPbBr3 Thin Films towards Enhanced Amplified Spontaneous Emission. (10th April 2021) - Li, Meili; Shang, Qiuyu; Li, Chun; Li, Shuai; Liang, Yin; Yu, Wenjin; Wu, Cuncun; Zhao, Liyun; Zhong, Yangguang; Du, Wenna; Wu, Xianxin; Jia, Zhili; et al.
Abstract: A solution‐processed thin film made of all‐inorganic CsPbBr3 perovskite is a promising candidate for low‐cost and flexible green‐color lasers. However, the amplified spontaneous emission (ASE) of solution‐processed CsPbBr3 films still experiences a high threshold owing to poor morphology and insufficient optical gain. Here, a multiple‐cation doping strategy is demonstrated to develop compact, smooth thin films of Cs0.87 (FAMA)0.13 PbBr3 /(NMA)2 PbBr4 (FA: formamidinium; MA: methylammonium; NMA: naphthylmethylammonium) with a record high net modal optical gain of ≈ 3030 cm −1 and low propagation loss of 1.0 cm −1 . The FA and MA cations improve the crystallization kinetics to form continuous films, and the NMA cations reduce the grain dimension, increase film dispersibility/uniformity, and enhance spatial confinement to promote optical gain. Room‐temperature ASE is demonstrated under a low threshold of ≈ 3.8 µ J cm −2 without degradation after four months of storage in glove box or excitation by 3 × 10 7 laser pulses. These findings provide insights into enhancing the optical gain and lowering the threshold of perovskite lasers in terms of molecular synthesis and microstructure engineering. Abstract : Gain/loss dynamics and low‐threshold amplified spontaneous emission of solution‐processed mixed‐cation CsPbBr3 perovskite films are demonstrated at room temperature. A long‐chain naphthylmethylammonium cation is introduced to reduce the grain dimension, improve film dispersibility/uniformity, and enhance spatial confinement, promoting a record high net modal optical gain up to ≈3030 cm −1 among the perovskite family.